Exploring Motives and Challenges in the Erasmus+ Student Mobility Program: A Case Study of Khazar University Students - Chirwa, Hamza (IIUM Journal of Educational Studies, 2025)
A significant advancement in educational mobility is the emergence of the Erasmus+ program, which has facilitated study experiences abroad for numerous students, including those from Azerbaijan. Among them is Khazar University where there is a noticeable gap in research regarding the motives and challenges encountered by students participating in the Erasmus+ program. Additionally, the challenges faced by these students remain inadequately addressed, largely due to the absence of comprehensive documentation and transparent reporting of participants’ experiences. In line with this, this mixed-methods research explores the motives and challenges experienced by Erasmus+ students from Khazar University. The study involved 16 students who participated in the Erasmus+ program between 2017 and 2023. All 16 students participated in a quantitative survey conducted via an online questionnaire. Subsequently, semi- structured interviews were held with seven of them to gather qualitative data. Using SPSS for analysis, the findings revealed that the primary motives for participating in the program include the opportunity to study abroad, meet new people, have fun, and gain independence or self-sustainability. Conversely, students perceived the pre-Erasmus period as the most challenging, with paperwork being the most daunting challenge. However, significant hurdles during the Erasmus program include variations in education systems, financial constraints, and culture shock. After the Erasmus period, many students grapple with what can be described as "post-Erasmus adjustment syndrome." The study will illuminate the policy makers and school administrators to address the identified challenges and tailor the students’ motives by providing comprehensive Erasmus+ information sessions, so the program should satisfactorily meet the expectations of the participants.